Autoregulation of H+/lactate efflux prevents monocarboxylate transport (MCT) inhibitors from reducing glycolytic lactic acid production - Blaszczak, W; Williams, H; Swietach, P (Springer Nature, 2022)
Background Pharmacological inhibition of membrane transporters is expected to reduce the flow of solutes, unless flux is restored (i.e., autoregulated) through a compensatory increase in the transmembrane driving force. Drugs acting on monocarboxylate transporters (MCTs) have been developed to disrupt glycolytic metabolism, but autoregulation would render such interventions ineffective. We evaluated whether small-molecule MCT inhibitors reduce cellular H+/lactate production.